Analysis of Factors Affecting the Implementation of Discharge Planning by Nurses in the Inpatient Ward: A Literature Review - I Made Yudi Wahyu; Ni Luh Putu Dina Susanti; I Gusti Ngurah Made Kusuma Negara; Ni Made Sri Rahyanti (Babali Nursing Research)
Introduction: Suboptimal discharge planning is a global issue that contributes to high patient readmission rates and increases the burden on healthcare systems. Effective discharge planning is essential to ensure the continuity of patient care after leaving the hospital, including follow-up care and maintaining the patient's health status. The purpose of this literature review is to identify the factors affecting the implementation of discharge planning by nurses in inpatient wards.